Effect of acid and oxidation degradation of gum arabic on the growth of Lactobacillus strains - Hamad Mohamad Salah Hamad Ahalil,; Shahrul Razid Sarbini,; Sahilah Abdul Mutalib,; Aminah Abdullah,; Mohamad Yusof Maskat, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Gum arabic consisted of polysaccharides that has the potential to be converted into oligosaccharides through degradation. Thus, this study aimed to determine the effect of gum arabic degradation on the growth of two Lactobacillus probiotic strains. Two types of gum arabic (Acacia senegal and Acacia seyal) were subjected to trifluoroacetic acid (TFA) and oxidation degradation. TFA degradation produced a significantly higher (p<0.05) degree of degradation for A. senegal (67.6%) and A. seyal (62.87%) compared to oxidation method for A. senegal (36.49%) and A. seyal (39.37%). Thus, TFA degradation was selected as the degradation method. The TFA treated gum arabic was used as growth medium for two types of probiotic strains namely, Lactobacillus plantarum and Lactobacillus reuteri. Results showed that OD of TFA treated gums from A. senegal (1.390) and A. seyal (1.330) was significantly higher (p<0.05) compared to untreated samples innoculated with Lactobacillus plantarum. Similarly, CDM of TFA treated gums innoculated with Lactobacillus plantarum for A. senegal (1.150 g/L) and A. seyal (1.050 g/L) was also significantly higher (p<0.05) compared to untreated samples. Using treated gum, the growth (OD and CDM) of Lactobacillus reuteri was significantly higher (p<0.05) compared to untreated gum. Prebiotic Index (Ipreb) of both types of treated gum arabic was significantly improved (p<0.05) compared to untreated samples. In conclusion, treating gum arabic from both Acacia senegal and Acacia seyal with TFA produced samples which were more favourable for the growth of Lactobacillus plantarum and Lactobacillus reuteri strains with significantly increased (p<0.05)I preb.